Assumptions, conjectures, and other miracles: The application of evalu ative thinking to theory of change models in community development - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie (Evaluation and Program Planning, 2016)
Unexamined and unjustified assumptions are the Achilles’ heel of devel opment programs. In this paper, we describe an evaluation capacity bui lding (ECB) approach designed to help community development practition ers work more effectively with assumptions through the intentional inf usion of evaluative thinking (ET) into the program planning, monitorin g, and evaluation process. We focus specifically on one component of o ur ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Za mbia. The use of ToC models, plus the addition of ET, is a way to enco urage individual and organizational learning and adaptive management t hat supports more reflective and responsive programming.
Keywords: Assumptions; Community development; Critical thinking; Evaluation capacity building; Evaluative thinking; International Development; Theory of change